NUMERICAL AND EXPERIMENTAL CALCULATION OF ROLL AMPLITUDE EFFECT ON ROLL DAMPING - Burak Yıldız; Ahmet Yurtseven; Toru Katayama; Bekir Şener (Brodogradnja, 2019)
Roll motion is still a challenging problem in naval architecture and an adequate prediction of this physical phenomenon is important because of its undesirable effects such as capsizing. There are several methods using linear potential theory to predict roll motion, such as strip method, however, the accuracy of the calculated results lag behind the accuracy of other degrees of freedom due to viscosity. Viscosity have an important effect on roll damping, especially near resonance, and as it is known, it is not included in potential flow methods. Vortex shedding is the main physical phenomena in viscous damping of the roll motion and it affects the flow velocity around the bilge. This may lead to pressure increase or decrease on the hull. In the present study, roll damping of a forced rolling hull with bilge keels at different roll amplitudes was calculated numerically by using an Unsteady Reynolds-averaged Navier–Stokes (URANS) solver. For the purpose of validation, forced roll experiments were carried out and the results were plotted next to numerical results. The generated vortices around the hull and bilge keel were observed in the URANS calculations. In the case of large roll amplitude motion, the vortex shedding from the bilge keel interacts with the free surface and leads to decrease on roll damping.